Implementasi Metode Langsung Dalam Meningkatkan Bahasa Arab - Maturidi Maturidi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
ABSTRACT In this study aims to find about the implementation of a direct method in improving Arabic in the Modern Ar-Ridho Sentul Pondok, as Arabic as the language of the Koran revealed by Allah to the prophet Muhammad SAW, while in this discussion produced several important points, among others, the application of the direct method of language improvement is done by creating a good language environment (bi'ah lugowiyah), all pondok residents speak Arabic without exception, making activities that support the implementation of Arabic language improvement methods, namely conversation, contest drama and others, in an effort to implement direct methods there are driving and inhibiting factors in applying these methods, the hope of this research is to provide benefits to all those who wrestle in their respective fields both, from education practitioners, boarding schools, or researchers and readers Keywords: Ar-Ridho, Arabic, direct method, teaching